A new Magneto‐Inductive tracking technique to uncover subterranean activity: what do animals do underground?. Issue 5 (26th February 2015) - Noonan, Michael J.; Markham, Andrew; Newman, Chris; Trigoni, Niki; Buesching, Christina D.; Ellwood, Stephen A.; Macdonald, David W.; Jones, Kate
Summary Despite the importance of the subterranean ecotope, knowledge of underground movement and behaviour has been extremely limited. Previous technologies have relied upon techniques with very low spatial or temporal resolution, such as VHF telemetry. Rather incongruously, therefore, relatively simple underground activity regimes have often been assumed, with insufficient attention to the ecological importance of burrow use. We test the capability of Magneto‐Inductive (MI) tracking, recording underground movement within a European badger sett over a 2 week period in February. These data allowed us to: quantify subterranean movement; extrapolate the three‐dimensional burrow architecture; simultaneously track multiple individuals; and establish the function of specific movement patterns; demonstrating the technique's utility. Contrasting data generated using MI tracking, against the resolution achievable with VHF tracking, we establish how sampling frequency can influence the perception of movement. Taking 20 locational fixes per minute, MI collars operated for 1 year before on‐board batteries failed, resulting in an average five billion data points per collar deployment. Socio‐ecologically we found that rather than foraging continuously throughout the night, badgers returned to the sett an average of 2·2 times, approximately every 3–4 h. From burrow mapping, badgers tended to use peripheral chambers for c. 45 min on these return visits. These outlying chambers were used less by day, when badgers selected deeper chambers, suggesting each chamber type fulfils a different function. This technology also exposed that badgers exhibited a far greater extent of underground movement than revealed by former technologies, which by comparison captured <0·5% of subterranean activity. Importantly, these high‐resolution data showed that individuals left, returned to, and moved about the sett independently, with no tendency for synchronous subterranean activity. In overview, Magneto‐Inductive tracking proved relatively simple and cost‐effective to deploy, it provided very detailed and accurate subterranean fixes, and was robust enough for long‐term field deployment. Furthermore, the capabilities of MI are highly transferable, enabling a better understanding of underground activity and the ecological importance of subterranean burrows for the conservation and management of a wide range of species.